Spinoza’ Politics - Jan-Erik Lane (New Horizons in Education and Social Studies Vol. 8, 2021)
In political thought, Hobbes and Spinoza form an interesting and fascinating couple. They lived parallel lives and wrote much on similar topics: humans, contracts, the state and religion. Whereas Hobbes is considered one of the absolute top political philosophers, Spinoza has only been recognized as a great philosopher, due to his Ethics. But on close examination, I dare say that Spinoza outperforms Hobbes also on political theory and religion. The aim of this paper is to call for a re-evaluation of Spinoza’s political and religious philosophy.